2017
DOI: 10.18632/oncotarget.17632
|View full text |Cite
|
Sign up to set email alerts
|

EMT circulating tumor cells detected by cell-surface vimentin are associated with prostate cancer progression

Abstract: Recent advances in the field of circulating tumor cells (CTC) have shown promise in this liquid biopsy-based prognosis of patient outcome. However, not all of the circulating cells are tumor cells, as evidenced by a lack of tumor-specific markers. The current FDA standard for capturing CTCs (CellSearch) relies on an epithelial marker and cells captured via CellSearch cannot be considered to have undergone EMT. Therefore, it is difficult to ascertain the presence and relevance of any mesenchymal or EMT-like CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 25 publications
3
107
0
Order By: Relevance
“…Third, mechanically, our previous study demonstrated that miR‐106b determines the effect of transforming growth factor β, a key EMT inducer, on the tumor behavior of breast cancer cells by targeting RB . Several studies have also demonstrated that a variety of genes were identified as the target of miR‐106b including caspase‐7 , PTEN , and Smad7 , which contribute to miR‐106b‐mediated EMT of cancer cells. In this scenario, CTC‐specific miR‐106b plays a critical role in regulating the EMT of CTCs, indicating that CTCs with higher expression of vimentin and miR‐106b show a higher motility in the bloodstream and more easily interact with the intravascular microenvironment, extravagate through the microvasculature, and interact with the metastatic microenvironment of target organs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Third, mechanically, our previous study demonstrated that miR‐106b determines the effect of transforming growth factor β, a key EMT inducer, on the tumor behavior of breast cancer cells by targeting RB . Several studies have also demonstrated that a variety of genes were identified as the target of miR‐106b including caspase‐7 , PTEN , and Smad7 , which contribute to miR‐106b‐mediated EMT of cancer cells. In this scenario, CTC‐specific miR‐106b plays a critical role in regulating the EMT of CTCs, indicating that CTCs with higher expression of vimentin and miR‐106b show a higher motility in the bloodstream and more easily interact with the intravascular microenvironment, extravagate through the microvasculature, and interact with the metastatic microenvironment of target organs.…”
Section: Discussionmentioning
confidence: 94%
“…Of note, the activation of an EMT is favorable for the CTC population . It has been reported that the presence of mesenchymal markers such as vimentin on CTCs more accurately predicted worse prognosis than the expression of cytokeratin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the role of the EMT process in drug resistance and tumor metastasis, EMT‐CTCs may be key determinants in the prediction of a prognosis in patients with advanced cancer (Mitra et al , ; Satelli et al , ; Satelli et al , ). Many researchers have investigated the enrichment of EMT‐CTCs in breast, colorectal and prostate cancers and their associations with aggressive phenotypes (Satelli et al , ; Satelli et al , ). Recently, we successfully demonstrated the detection of CTCs from peripheral blood samples of patients with advanced GC with high sensitivity based on an EMT‐CTC specific selection marker, CSV (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…AR‐positive and CD45‐negative circulating cells that are CK‐negative/weak have also been detected using the CellSearch platform . In a very recent study, it was shown that cell‐surface vimentin‐guided CTC enumeration may hold prognostic value and should be further validated as a possible measurement of PCa progression toward the deadly androgen‐independent form . The combination of in vivo CTC isolation with downstream RNA analysis is highly promising as a high‐throughput, specific, and ultrasensitive approach for multiplex liquid biopsy‐based molecular diagnostics for PCa patients .…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%